(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2020)
Introduction: Childhood tuberculosis has always been in shadows as Nepal’s Tuberculosis Program focused mainly on adults TB resulting in under diagnose with less than 10% of total TB cases notified. Lack of political commitment; absence of guideline and working group, qualified health personnel and diagnostics tool were major implementation challenges. Methodology: Assessment of childhood TB program was done and critical gap were identified. Childhood TB was prioritized in National TB strategic plan (2016-21). Collaborate with both international and national child experts, public and private organizations to develop guideline, building capacity of health care providers and establishing national working group. Childhood TB focused interventions were implemented in 40 high burden districts since March,2017 focusing on contact tracing, diagnosis, Prevention Therapy, malnourished children in the community and major hospitals. Results : Political commitment and multi-sectoral involvement, to manage childhood TB was achieved. A total of 93 doctors were trained in the Childhood TB management training and were identified as focal persons to manage childhood TB in their respective regions. Child focused intervention from March 2018-19 resulted in the diagnosis of 521 TB cases among 38,987 malnourished children and1,764 children were enrolled under TPT after contact tracing of 59,742 family members. With political commitment, prioritization of childhood TB, collaboration of both government and non-government sectors and interventions focusing childhood TB, a significant achievement can be attained in childhood TB management. Conclusion: Nepal has shown childhood TB management program can be strengthen if NTP prioritizes it, child focused interventions are implemented and collaborate with Child health division, pediatrics association, other government and non-government organizations to increase and strengthen the program.